PSYCHOLOGICAL PECULIARITIES OF COLLECTIVE ACTIVITY OF THE EMPLOYEES OF THE UKRAINIAN SSNS UNITS, MAIN FACTORS, EVALUATION CRITERIA AND INDICATORS OF ITS EFFECTIVENESS (Psychology Travelogs, 2025)
The article reveals the psychological features of collective activity of employees of the SES of Ukraine, identifies the main factors, evaluation criteria and indicators of its effectiveness. In particular, it is noted that The professional activity of employees who carry out professional activities within the units of the SES of Ukraine is a collective activity of a small group that has all its inherent features and a similar psychological structure. It is characterised by a number of specific features caused by the activity itself: clear regulation of activities by the requirements of current legislation, departmental guiding documents, service with weapons or special means, use of modern equipment and engineering means in professional activities. A significant distinguishing feature of the collective activity of the SESU employees is its extreme nature and stressfulness, and, accordingly, the presence of subjective, objective, socio-psychological, organisational and managerial stressors. The effectiveness of the collective activity of the SES of Ukraine unit staff is characterised by the degree to which its results meet the goals and objectives set out in the governing documents (regulatory legal acts governing professional activity and orders of senior management). It is influenced by many conditions and factors, such as the specifics of the team, the optimality of interactions, the strategy and tactics of joint group actions, the level of development of the group, leadership and management, the specificity and complexity of tasks, the duration of joint activities, the size of the group itself, the level of psychological stability and stress resistance, etc. The system for assessing the effectiveness of joint activity of the SESU unit's personnel is a set of criteria and indicators that allow determining not only the level of success of the service tasks assigned to the unit, but also the level of emotional satisfaction with the activity itself and the social and psychological maturity of the service team. Assessment ofthe effectiveness of the collective activity of the employees of the service team can be carried out according to two criteria: normative-productive and socio-psychological, each of which is revealed by a number of specific indicators.
Keywords: psychological characteristics; collective activity; employees; extremity; stressfulness